2021
DOI: 10.21203/rs.3.rs-501051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of E-Waste Exposure on Biomarkers of Coronary Heart Disease (CHD) and their Associations with Level of Heavy Metals in Blood

Abstract: Excess heavy metals increase the risk of various diseases. Electronic waste (e-waste) is a potential route to heavy metal exposure, and Taizhou is a large e-waste dismantling area in China. In this study, we acquire blood samples from residents living near an e-waste recycling area (exposed group) and other residents in a selected reference area (reference group) for a comparative study in Taizhou in December 2017. Seven heavy metals, including cobalt (Co), nickel (Ni), cadmium (Cd), tin (Sn), copper (Cu), zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…MTTP was also positively correlated with Cr. A study revealed that exposure to Cr, Cu and Zn caused lipid peroxidation and liver damage [73]. Another study found that high levels of Cr, Cu and Pb may be associated with changes in the risk of NAFLD [74].…”
Section: Correlation Analysismentioning
confidence: 99%
“…MTTP was also positively correlated with Cr. A study revealed that exposure to Cr, Cu and Zn caused lipid peroxidation and liver damage [73]. Another study found that high levels of Cr, Cu and Pb may be associated with changes in the risk of NAFLD [74].…”
Section: Correlation Analysismentioning
confidence: 99%